(3eMGSHI GdJcGdja GdRQGYjIs - (3LdGd(B, (3GMeOs; (3GjgGH fXej GHQGgje(B, s ((3YeGf(B:s (3ecJHI GdeLJeY GdYQHj(B,s, 2010)
(3GdGbJUGO GdRQGYj , GdRQGYI h GbJUGOjGJgG , eMGSHI GdJcGdja aj GdefTBJ GdRQGYjI , MSGHGJ GdGfTWI GdRQGYjI , MSGHGJ GdGfJGL GdMjhGfj (B.s
(3eQGLY U(B.223s
Keywords: (3GdRQGYIs; (3GdeMGSHIs; (3eMGSHI GdJcGdjas